Chief culture officer how to create a living, breathing corporation - McCracken, Grant David 1951- (Basic Books, 2009)
Grant McCracken, an anthropologist who now trains some of the world's biggest companies and consulting firms, argues that the American corporation needs a new professional--a Chief Culture Officer--who would keep a finger on the pulse of contemporary cultural trends while developing a systematic understanding of the deep waves of culture in America and the world.